Detection of Histoplasma capsulatum in Organic Fertilizers by Hc100 Nested Polymerase Chain Reaction and Its Correlation with the Physicochemical and Microbiological Characteristics of the Samples (2018)
ABSTRACT: Histoplasma capsulatum is the causative agent of histoplasmosis and this fungus inhabits soils rich in phosphorus and nitrogen that are enriched with bird and bat manure. The replacement of organic matter in agroecosystems is necessary in the tropics, and the use of organic fertilizers has increased. Cases and outbreaks due to the presence of the fungus in these components have been reported. The Instituto Colombiano Agropecuario resolution 150 of 2003 contains the parameters set by the Colombian Technical Standard (NTC 5167) on the physicochemical and microbiological features of fertilizers, but it does not regulate the search for H. capsulatum. The aim of this study was to demonstrate H. capsulatum presence in organic fertilizers by nested polymerase chain reaction (PCR). A total of 239 samples were collected: 201 (84.1%) corresponded to organic fertilizers, 30 (12.5%) to bird excrement, and 8 (3.4%) to cave soils. The Hc100 nested PCR had a detection limit of 0.1 pg/µL and a specificity of 100%. A total of 25 (10.5%) samples were positive and validated by sequencing. Seven of the positive samples represented locations where H. capsulatum was previously detected, suggesting the persistence of the fungus. No significant correlations were detected between the physicochemical and microbiological parameters with the presence of H. capsulatum by nested PCR, indicating the fungus existence in organic fertilizers that complied with the NTC 5167. The Hc100 nested PCR targeting H. capsulatum standardized in this work will improve the evaluation of organic fertilizers and ensure the prevention of outbreaks and cases due to manufacturing, marketing, and use of fertilizers contaminated with H. capsulatum.